Determination of birefringence of biological tissues using modified PS-OCT based on the quaternion approach - Ke, Qiuqing; Li, Ke; Wu, Weijie; Li, Wangbiao; Chen, Haiyu; Cai, Renhui; Li, Zhifang (Frontiers in Physics, 2023)
Introduction: Polarization-sensitive optical coherence tomography (PS-OCT) is a functional extension of standard OCT. PS-OCT systems can be generally categorized into two categories based on the number of input polarization states on the sample: multi-input polarization state (multi-IPS) and single IPS. In addition, each category includes two configurations: fiber-based system and bulk optics-based system. However, there are complex and time-consuming steps to calibrate the polarization states of light among the reference, the sample, and detection arms for fiber-based system. And it is not compact and robust enough for bulk optics-based system. Methods: In the modified SD PS-OCT system with structural symmetry in both arms of the reference and sample, there are no bulk polarization optical elements in both arms of the reference and the sample. A circularly polarized light was used to incident on sample, and Stokes vector of backscattered light was employed to characterize the birefringence of biological tissues based on the quaternion approach, which directly establishes the relationship between Stokes vectors of backscattered light and Jones matrix of the sample. Results and discussion: The new algorithm provides the analytic solution of retardance and fast-axis orientation. To evaluate the performance of the developed system, an eighth-wave plate is used. Then, the polarization properties of the myocardial tissue in vivo are quantitatively reconstructed based on the quaternion approach. The results demonstrated that the proposed method has an advantage over Jones formalism based on a single input state and two polarization input states. In the future, the modified SD PS-OCT could be improved as a common path SD PS-OCT for clinical applications.